Evidence for heterogeneity in recombination in the human pseudoautosomal region: high resolution analysis by sperm typing and radiation-hybrid mapping - Lien, Sigbjørn; Szyda, Joanna; Wogatzky, Birgit; Rappold, Gudrun; Arnheim, Norm (The American journal of human genetics, 2000)
Accurate genetic and physical maps for the human pseudoautosomal region were constructed by use of sperm typing and high-resolution radiation-hybrid mapping. PCR analysis of 1,912 sperm was done with a manual, single-sperm isolation method. Data on four donors show highly significant linkage heterogeneity among individuals. The most significant difference was observed in a marker interval located in the middle of the Xp/Yp pseudoautosomal region, where one donor showed a particularly high recombination fraction. Longitudinal models were fitted to the data to test whether linkage heterogeneity among donors was significant for multiple intervals across the region. The results indicated that increased recombination in particular individuals and regions is compensated for by reduced recombination in neighboring intervals. To investigate correspondence between physical and genetic distances within the region, we constructed a high-resolution radiation-hybrid map containing 29 markers. The recombination fraction per unit of physical distance varies between regions ranging from 13- to 70-fold greater than the genome-average rate.